Efek Samping Sectio Caesarea Metode ERACS (Literature Review) - Arifaa Thalitha Z.; Liana Sidharti; Evi Kurniawaty (Medula, 2023)
Sectio caesarea surgery or cesarean section is a labor procedure to remove the baby through an incision in the abdomen (laparotomy) and uterus (hysterotomy). These surgeries are increasing all over the world (ACOG, 2021). The level of this operation continues to increase as evidenced by the report from the World Health Organization or WHO which will be published in 2021. The research was conducted using the literature review method. Literature review is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing works. research results and ideas that have been produced by researchers and practitioners. The results of observations during the study on post-sectio caesarea (SC) birth mothers with the ERACS method, it was found that the implementation of early mobilization after 2-4 hours after surgery, most of the respondents were able to sit, and some even dared to stand. Then, after 8-10 hours, almost all of the respondents had removed the catheter, and some of the respondents had even taken a walk. After 13 hours after surgery, all respondents, based on the discussion above, which referred to several articles and journals, showed that the Caesarean section method had significant side effects, but there were also several advantages to the ERACS method, namely being able to make it easier and more effective in giving birth.